2019
DOI: 10.1590/0103-1104201912221
|View full text |Cite
|
Sign up to set email alerts
|

Gestão de eventos QBRN e a utilização do modelo Hysplit: uma revisão integrativa de literatura

Abstract: RESUMO O potencial risco de exposição das populações aos agentes Químicos, Biológicos, Radioativos e Nucleares (QBRN), seja por causas intencionais ou não, configura-se como questão de segurança nacional e demanda um constante aprimoramento do seu gerenciamento. Os modelos de dispersão atmosférica vêm ganhando destaque como ferramenta de apoio à gestão dos riscos aos agentes QBRN. O objetivo desta pesquisa foi identificar e avaliar estudos que utilizaram o modelo Hysplit no contexto de eventos QBRN. Para tanto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…It was noted that the selection of an ATDM for a specific study depends on its intended purpose, available release information and the computational resources. In a review of the dispersion modelling methods and tools employed in various countries, Pereira et al (2019) reported hybrid single-particle lagrangian integrated trajectory model (HYSPLIT) ATDM to be useful as part of a DSS during the different phases of management of CBRN events. Morino and Ohara (2016) performed a review on the use of modelling tools that were used for the estimation of the source term and the atmospheric dispersion of radionuclides after the Fukushima accident.…”
Section: Application Of Dss In Emergency Preparedness and Responsementioning
confidence: 99%
“…It was noted that the selection of an ATDM for a specific study depends on its intended purpose, available release information and the computational resources. In a review of the dispersion modelling methods and tools employed in various countries, Pereira et al (2019) reported hybrid single-particle lagrangian integrated trajectory model (HYSPLIT) ATDM to be useful as part of a DSS during the different phases of management of CBRN events. Morino and Ohara (2016) performed a review on the use of modelling tools that were used for the estimation of the source term and the atmospheric dispersion of radionuclides after the Fukushima accident.…”
Section: Application Of Dss In Emergency Preparedness and Responsementioning
confidence: 99%
“…According to the Brazilian constitution, in situations of this nature, the Armed Forces must act jointly, guided by the Ministry of Defense, in subsidiary actions supporting Civil Defense (1) . In addition to the concern with the use of this type of agent in attacks, under other circumstances, there is also the possibility of natural disasters triggering events involving CBRN agents, such as the one that occurred at the Fukushima Nuclear Power Plant in 2011, due to the tsunami generated after an earthquake (2) . It is noteworthy that disasters due to epidemics are also of national relevance in addition to the conflict situation itself.…”
Section: Introductionmentioning
confidence: 99%
“…CBRN events are recognized for their expressive ability to cause harm to human health or cause death. These events transcend the labor dimension, becoming a matter of national security and demand constant improvement in their management 2 . The impacts can be felt in several sectors, such as health and defense, reinforcing the need to develop technologies, contingency plans, public policies and training programs that can prevent future risks as well as prepare the agents and sectors involved to respond better to such events.…”
Section: Introductionmentioning
confidence: 99%